Muslim anti-secularist discourse in the context of Muslim-Christian relations - Zebiri, Kate (Islam and Christian-Muslim relations, 1998)
This article observes and critically evaluates some of the main components of Muslim anti‐secularist discourse: the assumption that there is ‘no separation between religion and politics’, that the Sharic a represents the antithesis of secularism, that secularism is a specifically Western or Christian phenomenon, and that secularism is causally related to a crisis of values in contemporary Western civilization. After observing some recent attempts to justify secularism on Islamic grounds, the article draws conclusions not just with respect to the discourse but also with regard to the underlying issues. The relevance of this topic to Muslim‐Christian relations emerges in two ways. Firstly, attention is paid to the way in which Christianity, or the West (the two are sometimes conflated), provides a significant Other for the purposes of self‐definition; and secondly, a comparative perspective on certain issues reflects shared concerns between Muslims and Christians on the role of religion in the modem nation‐state.